Smart Spaces - Azarbayejani, Ali; Wren, Christopher; Wilson, Andy; Becker, Dave; Oliver, Nuria; Roy, Deb; Sparacino, Flavia; Bérard, François (SIGGRAPH '96 ACM SIGGRAPH 96 Visual Proceedings: The art and interdisciplinary programs of SIGGRAPH '96, 1996)
Smart Spaces are ordinary environments equipped with visual and audio sensing systems that can perceive and react to people without requiring them to wear any special equipment. The "smart desk" research project consists of a self-calibrating visual system for 3D motion capture of a person, a face-tracking and facial-expression analysis system, and an audio-based expression and speech analysis system. Using these sensing systems, prototype applications have been developed for literal and non-literal physical and expressive animation of virtual characters that the user can interact with in real time. Smart Spaces was a booth in 1996 Siggraph Digital Bayou . The Bayou was a haven away from the vendor floor indended to showcase interesting research in graphics and interaction. More information on Smart Spaces can be found here.